Lessons from the collaborative innovation networks seminar. (2016) - Gloor, Peter A.; Paasivaara, Maria; Miller, Christine Z.; Lassenius, Casper
This paper describes lessons learned from teaching a distributed virtual course on collaborative innovation networks (COINs) over the last 12 years at five different sites located in four different time zones. The course teaches students how to leverage virtual collaborative creativity in the internet age by making best use of email, social media, and the web. In this paper we extend six principles of teamwork by Richard Hackman (2011) to the virtual realm.